2000
DOI: 10.1055/s-2000-6266
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of `Molecular Asterisks' via Sequential Cross-Metathesis, Sonogashira and Cyclotrimerization Reactions

Abstract: A series of suitably functionalized C-linked carbohydrate derivatives 9-13 were prepared in good yields from alkenyl glycosides 1-4 by cross-metathesis reaction using Grubbs' catalyst [Cl 2 (PCy 3 ) 2 Ru=CHPh]. The reaction was also applied to 6-O-allyl ether 5 and N-Cbz allylamine 6. C-Linked glycopeptide homologue 15 was prepared in 65% yield by cross-metathesis of perbenzylated b-C-allyl mannopyranoside 1 and allyl glycine derivative 8. Finally, amine-ending C-glycoside 11 was subjected to a sequence of dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 11 publications
1
19
1
Order By: Relevance
“…[62] An initial CM reaction between peracetylated a-d-allylgalactopyranoside 70 with protected amine 71 catalyzed by 6 afforded cross-product 72 in moderate yield with complete E selectivity (Scheme 13). The predominance of the E isomer in this CM reaction remains to be explained; CM reactions involving various other sugar derivatives under identical conditions gave selectivity no better than 4:1 in favor of the E form.…”
Section: Carbohydratesmentioning
confidence: 99%
“…[62] An initial CM reaction between peracetylated a-d-allylgalactopyranoside 70 with protected amine 71 catalyzed by 6 afforded cross-product 72 in moderate yield with complete E selectivity (Scheme 13). The predominance of the E isomer in this CM reaction remains to be explained; CM reactions involving various other sugar derivatives under identical conditions gave selectivity no better than 4:1 in favor of the E form.…”
Section: Carbohydratesmentioning
confidence: 99%
“…In 2001, Dondoni et al [12] conceived an olefin cross-coupling strategy that gave access to both C-glycosyl arganine and serine analogues. The authors point out that the only previously-reported cross metathesis strategy linked racemic allyl-glycine and a perbenzylated allyl β-D-Cmannoside derivative, as published by Roy and co-workers [13]. Dondoni and co-workers [12] reported that heating a mixture of allyl β-D-C-glucopyranoside 9, with vinyl oxazolidine 10, and the second generation Grubbs' catalyst in CCl 4 at 100 o C afforded the cross-metathesis product 11 in 50% yield as a mixture of E and Z isomers (Scheme (3)).…”
Section: Asparagine Derivativesmentioning
confidence: 99%
“…In contrast to reactions with organometallic reagents, the α-linked product was formed exclusively. The earliest olefin cross-metathesis approach for the formation of C-glycosyl analogues produced an unnatural amino acid derivative wherein a four-methylene chain connects the amino acid and sugar moieties [13]. Cross coupling of glycosyl derivative 75 and amino acid derivative 76 was carried out using Grubbs' first generation catalyst (Scheme (19)) to provide 77 as a mixture of E and Z isomers in 60% yield.…”
Section: C-linked Glycoconjugates With Unna-tural Spacing Between Carmentioning
confidence: 99%
“…A specific feature of this method is that the final glycosylamino acids can be easily incorporated in peptide-like glycoclusters or glycopeptides. The use of this method for synthesizing glycopeptide (11) and oligoglycine (13) scaffolds, [27] C-glycosyl oligopeptide (16), [28] as well as a synthesis of compounds based on C-fucosylpeptide (17) [29] have been reported. As a result, comparatively powerful P-selectinantagonists were obtained ( Figure 11).…”
Section: Transport Of Drugs and Genetic Materialsmentioning
confidence: 99%